Arbuscular mycorrhizal fungal inoculation improves Nauclea orientalis L. growth dan phosphorus uptake in gold mine tailings soil media - Faisal Danu Tuheteru; Asrianti Arif; H Husna; Irdika Mansur; Edy Jamal Tuheteru; J Jusniar; B Basrudin; A Albasri; Miranda Hadiyanti Hadijah; Sedek Karepesina (Brawijaya University, 2020)
Gold mine tailing soil media is characterized by low soil fertility and heavy metals toxicity. As an effort to improve the condition of gold mine tailing soil media, a revegetation experiment using Arbuscular Mycorrhizal Fungi (AMF) and soil media from gold mine tailing was conducted in the greenhouse. The objectives were to assess initial growth, P uptake and Pb reduction in Nauclea orientalis L. plants inoculated with indigenous AMF grown on gold mine tailing soil media. Three AMF fungi were used in this study, i.e. Glomus aggregatum, Glomus sp. and Acaulospora delicata. The experiment was conducted in Completely Randomized Design, having four treatments, i.e. control, G. aggregatum, Glomus sp. and A. delicata. The experiment was carried out for 3 months in a greenhouse scale. The results showed that local AMF inoculation significantly increased the height and stem diameter of lonkida by 181-213% and 284-443%, respectively, compared to control. The highest measurements of leaf’s length and width of lonkida seedlings were obtained from Glomus sp. and A. delicata treatments. Glomus sp. and A. delicata each significantly increased P levels in roots and shoots. Inoculation with G. aggregatum reduced Pb in the root and shoots parts by 74-86% and 72-76%, respectively, compared to controls. Local AMFs are potential to be developed as biological fertilizers to support revegetation in degraded lands, such as in gold mine tailing areas.